THE ACCOUNTING EXCHANGE. - Futhey, Bruce (The Accounting Review, 1941)
Accounting teaching can be divided into two phases, the classroom phase and the textbook phase. For many years accounting has been taught by the lecture method, the laboratory method, or by some combination of the two. Accounting teachers are indifferent to method. This is, perhaps, less true of high school teachers than of collegiate instructors, for the former have been exposed to "methods" courses in qualifying for teachers' certificates. Microfilm offers the first substantial contribution to accounting teaching in many years. There are, of course, certain limitations or disadvantages to accompany the benefits. Greatest is the limitation upon the amount of material which can be placed in one of the film "views." Writing or printing in illustrations must be somewhat larger than ordinary handwriting, so that when photographed and projected it will be legible for a reasonable distance. Other disadvantages are the cost, time involved in preparation of materials for photographing, and the necessity for adapting a classroom for projection.